Immune-checkpoint inhibitors in non-small cell lung cancer: A tool to improve patients' selection. (September 2018) - Banna, Giuseppe Luigi; Passiglia, Francesco; Colonese, Francesca; Canova, Stefania; Menis, Jessica; Addeo, Alfredo; Russo, Antonio; Cortinovis, Diego Luigi
Abstract: The identification of reliable predictive biomarkers of efficacy or resistance to immune-oncology (I–O) agents is a major issue for translational research and clinical practice. However, along with PDL1 and molecular features other clinical, radiological and laboratory factors can be considered for the selection of those patients who would not be the best candidate for immune-checkpoint inhibitors (ICPIs). We examined these factors, emerging from the results of currently available studies in non-small cell lung cancer (NSCLC), aiming to provide a useful and manageable tool which can help Oncologists in their everyday clinical practice. A thorough patient evaluation and close clinical monitoring, due to limited, early or inconclusive currently available data, should be deserved for patients with a pre-existing symptomatic chronic obstructive pulmonary disease, age >75 years, Eastern Cooperative Oncology Group (ECOG) performance status (PS) ≥ 1, a time to progression (TTP) < three months and progressive disease (PD) as the best response to the previous treatment, hepatitis or HIV-infections, high neutrophil to lymphocyte ratio (NLR), or on treatment with high-dose steroids, when the use of ICPIs is considered. Limited data are available to consider that ICPIs are safe in patients with interstitial lung disease, bronchiolitis obliterans organizing pneumonia and autommune diseases. Early evidence on steroids, vaccinations and antibiotics suggest their possible interaction with ICPIs and need to be more investigated in clinical trials. Oncogene-addicted NSCLC harboring EGFR-mutations and low tumor-infiltrating T-lymphocytes (TILs) seems not to gain benefit from I–O.